ANALISIS WACANA NASKAH DRAMA "ESOK DI NERAKA" - Denik Wirawan (Indonesian Language Education and Literature, 2015)
The analysis of discourse drama â€œEsok di Nerakaâ€ is analysis which recite the cosehiveness between cohesion and coherence in every dialog in that manuscript. The other aims of this analys is to describe part of instrument and shape of cohesion and coherence. The benefit of this research teoritically, used to the reader who want to research the discourse of drama. Beside that, reader can understand linguistic aspects in that discourse.